Dampak Penjajahan Belanda terhadap Budaya Maritim Indonesia dan Transformasi Identitas Nasional - Sarjito, Aris (Transbahasa, 2024)
This study investigates the dynamics of change in Indonesian maritime culture through an analysis of the role of Dutch colonization in the transformation of national identity. Drawing on qualitative research methods using secondary data, the study examines three key areas: factors contributing to Dutch colonization, the impact of Dutch colonial policies on traditional maritime practices and social structures, and the contribution of Dutch colonization to Indonesian national identity formation and its contemporary legacy. The research's findings show that trade interests, military conquests, and cultural exchanges were the driving forces behind Dutch colonization, which had a significant impact on Indonesian maritime culture. Dutch colonial policies such as the cultivation system and cultural assimilation efforts disrupted traditional maritime practices and social structures, leading to socio-economic disparities and cultural hybridization. However, Dutch colonization also fostered a sense of resistance and solidarity among Indonesians, contributing to the formation of a unified national identity. In conclusion, the study underscores the multifaceted nature of Dutch influence on Indonesian maritime culture and national identity, highlighting the enduring legacy of colonialism in contemporary Indonesian society.